Project-Based Learning: Lecturer Participation and Involvement in Learning in Higher Education - Pradana, Hirnanda Dimas (Journal for Lesson and Learning Studies, 2023)
Project-based learning greatly determines the participation and involvement of lecturers in the learning process. This study aimed to analyze the efficacy of project-based learning in increasing lecturer participation and involvement in learning in tertiary institutions. This study uses an evaluative approach to analyze whether project-based learning increases university-level lecturers' involvement and interest in their students' education. This study used a purposive sampling technique for sampling. Interviews and observation are two methods that fall into this category. Interview and observation are the two methods used in this research. The data was analyzed by comparing the participation and involvement of lecturers before and after implementing Project Based Learning. The results of this study indicate that Project Based Learning is effective for increasing the participation and involvement of lecturers in learning and assisting lecturers in developing their teaching abilities. Lecturer participation and involvement in learning-based initiatives in secondary education institutions will improve teaching quality and student learning outcomes. This study shows that increasing the use of project-based learning in tertiary institutions can increase the participation and involvement of lecturers in the learning process.